Relationship Between Percepted Control Behavior, Intention, Facility and Behavior of Debt Return - Santoso, Aprih; Nurhidayati; Susanto; Pratito, Dwi Widi (School of Business, IPB University (SB-IPB), 2024)
Background: Formulation of the problem for this research is, how will the role of intention as a mediating variable and facilities as a moderating variable be able to play a role in influencing perceived control behavior on debt repayment behavior.Purpose: This study empirically investigates the influence of perceived control behavior on debt repayment behavior, debt repayment intentions, and facilities on debt repayment behavior. Design/methodology/approach: Most of the determinants of research variables were developed based on the Theory of Planned Behaviour (TPB). Surveys to 120 people of owned Medium Small Enterprises (MSEs) in the culinary sector who took credit debt from the Wibawa government program in the city of Semarang. Data were analyzed using the structural equation model (SEM PLS)Findings/Result: The results showed perceived control behavior had a positive effect on the intention to repay the debt of MSE owners who took out Wibawa's credit debt. Furthermore, perceived control behavior and debt repayment intention have a positive effect on debt repayment behavior. We found empirical evidence that facilities have a role in strengthening the influence of debt service intentions on debt service behavior. Conclusion: This study enhances the behavioral debt literature by employing more extensive measures to assess perceived control, behavior, and intention, while also introducing the use of facilities as an alternative measure for variables that reinforce behavioral intention.Originality/value (State of the art): The originality lies in its contribution to the existing literature on debt behavior, as it utilizes two dimensions to measure behavior and introduces facilities as a novel reinforcement measure. Keywords: return behavior, debt facilities, culinary MSMEs, control behavior